Sex disparity in laparoscopic bariatric surgery outcomes: a matched-pair cohort analysis - Pouria Mousapour (Nature Portfolio, 2021)
Abstract Men have been historically considered to be higher-risk patients for bariatric surgery compared to women, the perception of which is suggested to be a barrier to bariatric surgery in men. The purpose of this study is to conduct a matched-pair analysis to evaluate sex disparities in laparoscopic bariatric surgery outcomes. Data on patients who underwent laparoscopic bariatric surgery from March 2013 to 2017 was collected prospectively. Then, 707 men and 707 women pair-matched for age, preoperative body mass index (BMI) and the procedure type (i.e., sleeve gastrectomy, Roux-en-Y, or one-anastomosis gastric bypass) were compared in terms of weight loss, remission of obesity-related comorbidities, and postoperative complications classified according to the Clavien–Dindo classification. There was no difference between the two sexes regarding the operation time, bleeding during surgery and length of postoperative hospital stay. We observed similar total weight loss, BMI loss, and percentage of excess BMI loss at 12, 24, and 36 months postoperatively between men and women, with no difference in remission of diabetes mellitus, hypertension and dyslipidemia at 12 months. The rate of in-hospital, 30-day and late complications according to Clavien–Dindo classification grades was similar between men and women. Our matched-pair cohort analysis demonstrated that bariatric surgery results in comparable short- and mid-term efficacy in men and women, and is associated with similar rate and severity of postoperative complications between sexes. These findings suggest bariatric surgeons not to consider sex for patient selection in bariatric surgery.